Mengukur Peran Manajemen Pengetahuan, Human Capital, dan Inovasi dalam Memengaruhi Kinerja Guru [Measuring the Role of Knowledge Management, Human Capital and Innovation in Influencing Teacher's Performance] - Octavia Marlene Wijaya (Jurnal Ketopong Pendidikan, 2022)
The purpose of this research was to know the influence of knowledge management, human capital and innovation to the school’s performance at school X in Tangerang. The data collection was held using questionnaires from the populations of teacher in senior high school which was 42 teachers. The research methodology of this research was quantitative with path analysis to find the correlation between variables. The data processing used PLS-SEM method. The result of this research was that knowledge management influenced positively 0,690 to the human capital, knowledge management influenced positively 0,424 to the innovation, knowledge management influenced positively 0,185 to the performance of the organization, human capital influenced positively 0,533 to the innovation, and innovation influenced positively 0,698 to the performance of the organization. Human capital influenced negatively 0,018 to the performance of organization. This research found that there was a need of an improvement of human capital management especially in teacher’s turnover to avoid the loss of intangible asset, knowledge to maintain the performance of School X for long term. It was found that it was needed that the development of knowledge transfer as a part of knowledge management in School X to keep knowledge retention so in the future, the existed human capital would be able to produce innovation and maintain for the long term’s performance.